The impact of liberalization on uncovered interest rate parity - Chuan, Annie (2003)
This study make use of the uncovered interest rate parity (UIRP) relationship to examine the extent that the liberalization of emerging financial markets has resulted in the integration of developing countries' currency markets into the international capital market. Previous tests of the impact of liberalization on the integration of emerging capital markets into world financial markets are confined to equity markets, ignoring currency markets that are arguably more important in determining the success of financial liberalization. This study finds that deviation from UIRP in the emerging markets is systematic in nature and that a significant part of emerging market currency excess returns is attributable to a time-varying risk premium. This study also finds that these countries'currency deposits provide US (equity) investors with the benefits of international diversification. The results show that for some markets, liberalization improved (worsened) investors' perception of growth opportunity while reducing (increasing) investors' perception of the probability of financial distress. Finally, while several countries benefited from liberalization and have become more integrated into the world capital market, the experience is country specific.